The Higher Education of the Young. - Sadler, S. H. (Routledge library editions. Education., 2011)
Taking into account the rapid progress in all areas of life that was made at the turn of the 20th century this volume discusses how best to educate both sexes, from all social classes, referring to Greek, Roman and Egyptian education as a starting point.